Expansão de células-tronco mesenquimais em frasco spinner com microcarregadores - Sanches, Simone (2010)
The Mesenchymal Stem Cells (MSCs) from adult tissues are at present an attractive source for applications in tissue engineering and cellular therapies. It presents a potential to differentiate into different cell lines as adipocytes, chondrocytes, osteocytes and myocytes. Due to low availability in the tissues and the fact that the demand for therapeutic applications is much larger than the supply capacity has become necessary to expand them in vitro strongly dependent on conservation of their differentiation potential. The MSCs are anchorage dependent, they have the characteristic of adhering to a solid substrate for subsequent proliferation. The conventional procedure of expansion in T-flasks with growth in monolayers, usually involves a difficult monitoring and control process, with high contamination indexi, low cell yield and high cost. In this work, we evaluated a methodology of expansion of hMSC-TERT line in spinner flask with microcarriers (small particles with properties favorable for cell adhesion and proliferation). In the experiments, two type of microcarriers were used, Cytodex 1 non-porous and with positive electric charge and Cultispher S, macroporous and electrically neutral, both in stirred spinner flask of 100 mL in culture medium α-MEM with 15% fetal calf serum, maintained in a CO2 incubator at 37°C and pH between 7.2 and 7.4. To increase productivity, some strategies were adopted during the research as a nutritional balance of the culture medium, addition of microcarriers and dilution and/or replacement of medium during cultivation. Aided by analysis of metabolites by high performance liquid chromatography and optical microscopy, the results showed that it was possible to grow hMSC-TERT with two microcarriers while maintaining good conditions for growth in three dimensions. However, the cell yield was limited mainly by the formation of clusters of microcarriers/extracellular matrix and is possible to obtain a cellular expansion factor of 4.98 with Cytodex 1 and 9,70 with Cultispher S. Because of the easy recovery of the cell showed by later microcarrier, it was performed an analysis of the maintenance of antigenic phenotype by flow cytometry and induction of differentiation into adipocytes and osteocytes. The results confirmed the conversation of phenotypic characteristics of hMSC-TERT with the cultivation technique evaluated in this work.